Non-living Biomass of Water Hyacinth Roots as a Sorbent for Chromium (ITI) in Aqueous Solution - Low, K. S.; Lee, C. K. (Universiti Putra Malaysia Press, 1997)
The ability of the non-living biomass of water hyacinth roots, Eichhomia crassipes, to remove Cr(lll) has been studied at different concentrations, pH levels and in the presence of Na and Ca ions in an attempt to simulate the real conditions of tannery waste. Ca ions exhibited a greater inhibitory effect on the Cr(lll) sorption than the Na ions. Kinetic studies showed that more than one mode of sorption was operating in the uptake of Cr(lll) by water hyacinth roots. The equilibrium data obeyed Langmuir isotherm for the Cr(III)-water hyacinth root system, implying mono-layer coverage of the sorben t material.